Digital Opportunities and Threats of Organization in New Economy - O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The subject of the research presented by the article is opportunities and threats for the organization, which are carried by digital era. The author provides characteristic of the three industrial revolutions that already took place and describes prospects of the fourth one that we witness right now. Its foundation is formed by interaction of industrial and digital technologies and its precondition is mass spread of the Internet. The article gives a list of key technologies, whose combination could seriously raise the efficiency of organization work. It includes the Internet of things, mobile devices and applications, cloud calculations, cyber-physical systems, analysis of big data and new industrial technologies. The author divides digital opportunities into 4 groups: industrial, market, logistic and organizational-managerial. It is also underlined that besides vast opportunities digitalization implies threats: socialeconomic, technological, ecological and informational. Principle problems, which hinder home organizations to integrate into digital economy, were studied. At the same time the level of using new technologies by Russian enterprises and index of business digitalization were analyzed. In conclusion the author substantiates the necessity to introduce digital technologies to ensure competitiveness of companies in new economy.